EKOLOGI CAPUNG JARUM CALOPTERYGIDAE: Neurobasis chinensis DAN Vestalis luctuosa DI SUNGAI CIKANIKI, TAMAN NASIONAL GUNUNG HALIMUN - Aswari, Pudji (Research Center for Biology-Indonesian Institute of Sciences, 2004)
Studies on ecological aspects of two species of damselflies, Neurobasis chinensis and Vestalis luctuosa (Odonata:Calopterygidae) were conducted at Cikaniki stream, Taman Nasional Gunung Halimun (TNGH).The two species of damselflies were selected from 26 species of dragonflies that have been collected in the study area.Selection was based on their appearance which is big in size, metallic colour are conspicuous and also on the habitat specificity.